Navigating Global vs. Local Tensions in Multinational Corporations: The Paradoxical Responses of Local Managers to Competing Demands - Keh, Pauline; Thelisson, Anne-Sophie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
Torn between pressures coming from their global and their local environments, multinational subsidiary managers are often confronted with multiple and sometimes conflicting demands. In this inductive research we propose to mobilize paradox theory in order to investigate the process through which local managers navigate paradoxical tensions in their practices. Based on an in-depth case study of a French manufacturing site of IBM, our research reveals that local managers often struggle with belonging and performing paradoxical tensions and that they may navigate such tensions by adopting paradoxical responses—transgressive alignment, obedient deviance—that simultaneously combine elements of compliance and non-compliance.